Child Labor and Learning - Emerson, Patrick M.; Ponczek, Vladimir; Portela Souza, Andre (World Bank, Washington, DC, 2014)
This paper uses a unique micro panel dataset of Brazilian students to investigate the impact of working while in school on learning outcomes. The potential endogeneity is addressed through the use of difference-in-difference and instrumental variable estimators. A negative effect of working on learning outcomes in math and Portuguese is found. The effects of child work range from 3 to 8 percent of a standard deviation decline in test score, which represents a loss of about a quarter to a half of a year of learning on average.